2000
DOI: 10.1590/s0101-81752000000200004
|View full text |Cite
|
Sign up to set email alerts
|

Cardumes da sardinha-verdadeira, Sardinella brasiliensis (Steindachner), em águas costeiras do estado do Rio de Janeiro, Brasil

Abstract: ABSTRACT. Schools ofBrazilian-sardinc, Slmline/lll brasiliensis (Stcindachncr), in coastal waters of Rio de Janeiro State (Brazil). This paper deals wilh the OCCUlTence and schol sizes of the Brazilian-sardine, Sordil/e/lo brosi/iensis (Steindachner, 1879), in coasla l waters of Rio de Janeiro State (Brazil), during the years 1993-1997. The schools are more Ii'equent and heavier in bay and surroundings of Grande Island; another area, with lesser importance, remains between the Cape ofSão Tomé and surroundings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
1
6
0
2
Order By: Relevance
“…Thus, it is necessary to perform more coordinated tactics to catch prey in large schools, such as Cupleidae and Engraulidae, during this period (MATSUURA 1978). Despite the fact that S. brasiliensis occurs in both areas, PAIVA & MOTTA (2000) reported that the larger and heavier schools of species near the state of Rio de Janeiro were found in waters of the Ilha Grande Bay, corroborating our hypothesis. However, in the Sepetiba Bay, the duration of feeding bouts and the frequency of feeding tactics were higher during the autumn-winter period, with the wall formation and kettle being more frequently used during this season.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, it is necessary to perform more coordinated tactics to catch prey in large schools, such as Cupleidae and Engraulidae, during this period (MATSUURA 1978). Despite the fact that S. brasiliensis occurs in both areas, PAIVA & MOTTA (2000) reported that the larger and heavier schools of species near the state of Rio de Janeiro were found in waters of the Ilha Grande Bay, corroborating our hypothesis. However, in the Sepetiba Bay, the duration of feeding bouts and the frequency of feeding tactics were higher during the autumn-winter period, with the wall formation and kettle being more frequently used during this season.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, Bryde's whales showed low occurrence in the area during the winter season, which may be explained by the low occurrence of Brazilian sardines ( Sardinella brasiliensis ) in the same area during this season (Paiva & Motta, 2000). Bryde's whales are also known locally as ‘ baleia-sardinheira ’ (sardine whale), due to frequent observations of this species feeding on Brazilian sardines, and the Cabo Frio region is one of the areas that displays the highest abundance of these fish (Paiva & Motta, 2000). The distribution and movements of this whale species are thought to be influenced by its prey dynamics (Zerbini et al ., 1997; Wiseman et al ., 2011; Dywer et al ., 2016).…”
Section: Discussionmentioning
confidence: 45%
“…In spite of their low economic value, they represent a resource of interest, for instance, when the Brazilian sardine occurs in great volumes. The production peak in the fall, matches the highest frequency of sardine schools in coastal waters of Rio de Janeiro State, after reproduction (Paiva & Motta, 2000).…”
Section: Discussionmentioning
confidence: 55%